2011
DOI: 10.1094/cchem-08-10-0121
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Agronomic Effects of Three High‐Molecular‐Weight Glutenin Subunit Transgenic Events in Winter Wheat

Abstract: Quality and agronomic effects of three transgenic high molecular weight glutenin subunit (HMW‐GS) events were characterized in advanced‐generation breeding lines of hard winter wheat (Triticum aestivum L.) in three Nebraska crop years. Two of the transgenic events studied, Dy10‐E and B52a‐6, overexpress HMW‐GS 1Dy10, while the third event, Dx5 +Dy10‐H, overexpresses HMW‐GS 1Dx5 and, to a much lesser extent, 1Dy10. In addition, novel proteins possessing solubility characteristics defined as HMW‐GS were present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
(6 reference statements)
0
19
0
Order By: Relevance
“…42 While these studies have shown that different HMW-GS can have distinct effects on dough mixing properties, ultimately it is desirable to introgress transgenes from Bobwhite into advanced cultivars by conventional breeding to truly assess the effects of the transgenes on flour quality. 43,44 Only a few transgenic studies using Bobwhite have focused on gluten proteins from the more complex LMW-GS and gliadin families. Masci et al 45 overexpressed a LMW-GS and Gil-Humanes et al 46 used RNA interference to silence gamma gliadin genes.…”
Section: Transformation Of the Us Bread Wheat 'Butte 86' And Silencinmentioning
confidence: 99%
“…42 While these studies have shown that different HMW-GS can have distinct effects on dough mixing properties, ultimately it is desirable to introgress transgenes from Bobwhite into advanced cultivars by conventional breeding to truly assess the effects of the transgenes on flour quality. 43,44 Only a few transgenic studies using Bobwhite have focused on gluten proteins from the more complex LMW-GS and gliadin families. Masci et al 45 overexpressed a LMW-GS and Gil-Humanes et al 46 used RNA interference to silence gamma gliadin genes.…”
Section: Transformation Of the Us Bread Wheat 'Butte 86' And Silencinmentioning
confidence: 99%
“…The major advantage of the Mixograph method is that it is not time consuming and it requires small amount of flour sample (2g, 10 g and 35 g depending on mixing bowls). Therefore, this method remained traditional among breeders, who handle with small amounts of sample, and for whom this method was initially designed (Graybosch et al, 2011).…”
Section: Mixographmentioning
confidence: 99%
“…This line was crossed with Great Plains winter wheats and further characterized in those backgrounds (Graybosch et al, 2011). Seeds from these derived lines can contain seed storage proteins other than those in the transformed cultivar 'Bobwhite' (BW in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The derivation and characterization of those lines are described in Graybosch et al (2011). The original 'Bobwhite' transformant was co-transformed by Ubi::BAR and a plasmid carrying the native gene encoding 1Dy10.…”
Section: Derivation Of Transformed Linesmentioning
confidence: 99%